Problems and Prospects of Innovative Development of Petrochemical Enterprises - Lenkova, Olga Viktorovna; Permyakov, Anton Stanislavovich; Yakunina, Olga Gennadyevna; Vechkasova, Marina Vyacheslavovna (International Journal of Energy Economics and Policy, 2017)
The article reveals that the petrochemical sector of the Russian economy has great potential for development while remaining one of the most underperforming sectors of the domestic economy compared to the world level. Under the current conditions, the most significant task of the state and top management of petrochemical companies is innovative development of oil and gas chemistry with the purpose of improving the competitiveness of domestic products on the world markets. Findings of the analysis of conditions and factors that result in the low level of development of the Russian chemical industry are provided in order to substantiate the possibilities for the further development of petrochemistry. The factors defining the innovative activity of enterprises in the sector are indicated. Perspective tasks and problems that need to be solved to bring petrochemistry in Russia to the innovative path are presented. Sectoral specifics of petrochemical enterprises and their current state are indicated as the main reasons that hamper this process. The need for significant investment for a long period of time makes the companies unattractive to potential investors and necessitates the use of state regulation measures in innovative processes in petrochemistry. Keywords: Innovative development, petrochemical enterprise, problems, prospects. JEL Classifications: O31, O32